NOTES ON MALESIAN NAUCLEEAE - C E Ridsdale (REINWARDTIA, 2008)
RIDSDALE, C.E. 2008. Notes on Malesian Neonaucleea. Reinwardtia 12(4): 285 – 288 — Neonauclea pseudoborneensis, Neonauclea subsessilis and Myrmeconauclea surianii are described as new species.Sarcocephalis fluviatilis Elmer is reinstated as a variety of Myrmeconauclea strigosa.The loss of a large number of type specimens formerly in L is reported.